Pengaruh Exchange Rate, Inflasi, Leverage, dan Firm Size Terhadap Volatilitas Harga Saham (Studi Kasus pada Perusahaan IDX30 di Bursa Efek Indonesia Periode 2018-2022) - Fitriani, Wulan; Desmiza, Desmiza (J-MAS (Jurnal Manajemen dan Sains), 2024)
IDX30 companies experienced significant volatility in 2020 due to the COVID-19 pandemic, resulting in uncertainty regarding their stock returns. This information led to fluctuations in stock prices. This research aims to investigate the influence of exchange rates, inflation, debt, and firm size on stock price volatility. Using purposive sampling, 12 IDX30 companies were selected as samples for the period 2018-2022. Data samples were collected from annual financial reports via the Indonesia Stock Exchange and Bank Indonesia's website. This study employs panel data analysis, descriptive analysis, panel data regression analysis, regression analysis, and coefficient determination analysis. The research findings indicate that exchange rates and inflation don’t affect on stock price volatility, whereas leverage and firm size significantly influence stock price volatility. The test results also demonstrate that exchange rates, inflation, leverage, and firm size collectively influence stock price volatility. The R-squared value is 99.99 percent, suggesting that 99.99 percent of the variation in the dependent variable can be explained by variations in the independent variables within the testing model.